Do bank shocks affect physical or R&D investments more? Evidence from Japan - Mizobata, Hirokazu (Journal of Corporate Finance, 2023)
This study focuses on physical and R&D investments to examine the effect of bank shocks on corporate investment behavior at the firm and economy levels. I use matched bank-firm lending data for listed Japanese companies from 1990 to 2013 to distinguish bank loan supply shocks from firms’ borrowing shocks. Notably, bank concentration increased in Japan during this period, thereby enhancing the granularity of bank shocks. The estimation result of each investment function reveals that bank shocks become highly relevant for firms’ physical investment relative to their R&D investment. Specifically, a negative bank shock of one standard deviation decreases the physical (R&D) investment rate by 12.6% (less than 1%) for firms with the median level of debt ratio. Consistent with this, the economy-level analysis shows that granular bank shocks account for 9.4% of the variation in Japan’s aggregate physical investment but have no explanatory power for the country’s aggregate R&D investment.